Agar oligosaccharides: A review of preparation, structures, bioactivities and application. (1st August 2021) - Chen, Xiaodan; Fu, Xiaoting; Huang, Luqiang; Xu, Jiachao; Gao, Xin
Highlights: The differences of AOs obtained by chemical and enzymatic degradation. The summary of separation, purification methods, and structure of AOs. The summary of series of biological activities of AOs like antioxidant, etc . Correlation between biological activities of AOs with Mw, DP and sulfate group. Abstract: Agar, a gelatinous polysaccharide which is in the cell wall of many red algae, is widely used as food and gelling agent. Agar oligosaccharides (AOs), the hydrolysate of agar, show much more kinds of bio-activities because of its lower molecular weight, better water solubility and higher absorption efficiency. It is indicated that AOs with different structure and degree of polymerization, i.e. series of agaro-oligosaccharides and neoagaro-oligosaccharides, can be obtained under different preparation conditions. In addition, the biological activities of AOs are diversely and closely correlated to the composition and structure. This review aims to comprehensively summarize the preparation, structural characteristics and bio-activities of AOs, so as to provide a reference for applications of AOs as marine natural products in pharmacological, cosmetics and nutraceutical fields.